The Inhibitory Effects of Pentacyclic Triterpenes from Loquat Leaf against Th17 Differentiation. (17th August 2020) - Zhou, Xiaoqing; Chen, Huanpeng; Wei, Fengjiao; Zhao, Qingyu; Su, Qiao; Lei, Yu; Yin, Meng; Tian, Xuyan; Liu, Zhonghua; Yu, Bolan; Bai, Chuan; He, Xixin; et al.
ABSTRACT: Background: Loquat leaf is an herb that is commonly used in traditional Chinese medicine (TCM) for its anti-inflammatory properties. Numerous studies have demonstrated that Th17 cells play a fundamental role in mediating SLE pathological deterioration. In our study, we investigated the inhibitory effect of pentacyclic triterpenes from loquat leaf on T helper 17 (Th17) cells and the therapeutic efficacy of OA in Lupus nephritis (LN) development. Methods: We isolated three pentacyclic triterpene compounds rom loquat leaf by bioassay-directed fractionation and separation method. There were methyl corosolate (MC), uvaol (UL), and oleanolic acid (OA) Firstly, we elucidated Retinoic acid receptor-related orphan receptor gamma t (RORγt) inhibitory activity of these three compounds in the cell-based assay and Th17 differentiation in vitro assay . Then, we used OA-treated pristine-induced LN mice to evaluate the therapeutic effects of OA in LN development. Anti-dsDNA level in serum was detected by enzyme-linked immunosorbent assay (ELISA), interleukin 17A (IL-17A) and interferon-γ (IFN-γ) expression in spleen cells by Flow cytometry (FCM), histomorphologic examination of kidneys were performed by periodic acid schiff (PAS) staining and immunofluorescence analysis. Results: Pentacyclic triterpene compounds (MC, UL, OA) displayed inhibition of RORγt activity in cell-based assay and Th17 differentiation in vitro . Furthermore, our results also showed that OA could significantly decrease serum anti-dsDNA antibody levels, IL-17A and IFN-γ expression and alleviate renal pathological damage in OA-treated group mice than in the model group mice. Conclusion: These results demonstrated that OA can improve the clinical manifestation of LN, indicating potential application in SLE therapy.